A perturbed utility route choice model. (March 2022) - Fosgerau, Mogens; Paulsen, Mads; Rasmussen, Thomas Kjær
Abstract: We propose a route choice model in which traveler behavior is represented as a utility maximizing assignment of flow across an entire network under a flow conservation constraint. Substitution between routes depends on how much they overlap. The model is estimated considering the full set of route alternatives, and no choice set generation is required. Nevertheless, estimation requires only linear regression and is very fast. Predictions from the model can be computed using convex optimization, and computation is straightforward even for large networks. We estimate and validate the model using a large dataset comprising 1, 337, 096 GPS traces of trips in the Greater Copenhagen road network. Highlights: Traveler behavior represented as a utility maximizing flow across an entire network. Substitution between routes depends on how much they overlap. The model is estimated using all route alternatives, and no choice set generation is required. Estimation is very fast. Predictions computed using convex optimization. Estimate and validate the model using 1, 337, 096 trips in large road network.